Comparative analysis of the characteristics of school education and furnishings in the youth and old adult age schools (Actual Problems of Psychology in Educational Institutions, 2019)
The article explores the features of school anxiety andfrustration among students of younger and older adolescents. Attention isfocused on the causes of the appearance of these states. One of the mainproblems of the emergence of frustration is not only changes in the socialenvironment but in the physiological context. The results of the study offrustration and anxiety in their inseparable connection are presented. It is notedthat adolescent students are characterized by high levels of anxiety. And alsothey have an extrapunitive reaction to the frustrator. Revealed the reasons forthe high rate on a scale of "frustration needs to achieve success".
Keywords: frustration, anxiety, interrelation of frustration and anxiety, empirical research, types of reactions to the frustrator, extrapunitive and intrapunitive reactions, Phillips school anxiety test, the “picture frustration” technique S. Rosenzweig, pupils of younger and older adolescence